Ru-based olefin metathesis catalysts bearing ph-responsive n-heterocyclic carbene (NHC) ligands: Activity control via degree of protonation - Balof, S.; Yu, B.; Lowe, Andrew; Ling, Y.; Zhang, Y.; Schanz, H. (Wiley - V C H Verlag GmbH, 2009)
Olefin metathesis catalysts (H2ITap)(PCy3)Cl2Ru=CHPh (4)and (H2ITap)Cl2Ru=CH-(C6H4-O-iPr) (5)[H2ITap = 1,3-bis-(2-,6-dimethyl-4- dimethylaminophenyl)-4,5-dihydroimid-azol-2-ylidene] were used for the ring-opening metathesispolymerization (ROMP) of exo-7-oxanorbornene derivative 7in the presence of various amounts of acid. Upon gradualprotonation of the NMe2 groups of the H2Tap ligand, the me-tathesis activity of both catalysts were gradually reduced dueto electronic changes of the N-heterocyclic carbene (NHC)ligand donor capability. The investigation of the ROMP poly-mer 8, DFT calculations and measurements of the initiationkinetics prove that the reduced activity is solely due to re-duced rates of propagation. © Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009.